Usefulness of direct intratumoral administration of doxorubicin hydrochloride with an electro-osmosis–assisted pump - Ito, Ayu; Itakura, Shoko; Hasegawa, Yuya; Hashimoto, Miyu; Okada, Akie; Hirafuji, Mamoru; Nakamura, Hidenori; Sugibayashi, Kenji; Todo, Hiroaki (Frontiers in Drug Delivery, 2023)
Patients receiving chemotherapy by intravenous (i.v.) or oral administration of anticancer drugs often experience side effects. In this study, an electro-osmotic flow (EO) pump was used for the direct administration of an anticancer drug with minimum side effects. Doxorubicin hydrochloride (DXR) was used as an anticancer drug, and its antitumor effect and toxicity were evaluated in comparison with i.v. administration. Balb/c female mice were subcutaneously transplanted with a breast cancer cell line (4 T1/Luc) stably expressing luciferase, and 20 μL of DXR solution (1.0 mg/mL) was administered intratumorally (i.t.) at a slow rate (0.6 µL/min) using an EO pump or rapidly using a syringe. For comparison, 100 μL of DXR solution was injected through the tail vein at the same dose and a 5-times higher dose. A tumor growth inhibitory effect without significant weight loss was observed with direct i.t. administration of DXR using an EO pump. On the other hand, no suppressive tumor growth effect was observed with i.v. administration of DXR at the same dose. Although there was no significant difference in the suppression effect on tumor growth between i.t. administration with EO pump and syringe, the peripheral skin concentration of DXR were decreased after slow administration with EO pump compared with that after rapidly administration with a syringe. These results indicated that direct i.t. administration of DXR with lower dosing using an EO pump at slower administration rate may be useful for exhibiting antitumor effects and suppressing systemic side effects. In addition, the blood concentration and the peripheral skin concentration of DXR after administration at lower rate with EO pump were decreased compared with those after the rapidly administration with a syringe.